Investasi Emas Digital Di Indonesia Berdasarkan Prinsip Hukum Ekonomi Syariah - Nazla Arliva Rahman; Baidhowi Baidhowi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Digital gold investment is growing rapidly as a modern investment alternative that combines financial technology (fintech) with conventional commodities. However, from a sharia economic law perspective, this investment faces a number of serious challenges. The main issues include the requirement for physical gold ownership underlying digital transactions, the clarity of the sharia contract used, and weak regulation and supervision of fintech platforms. Additionally, legal and Islamic risks also arise from the security of third-party storage and the low level of public literacy regarding Islamic investment principles. This article examines these challenges in depth and provides recommendations to strengthen the legal and Islamic foundations of digital gold investment.